2008
DOI: 10.1631/jzus.b0820154
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of extracts from Hong Kong seaweeds

Abstract: Abstract:We extracted six Hong Kong brown seaweed species with hot water for their antiviral properties. The cytotoxicity and antiviral activity of these extracts were tested by MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenlytetrezolium bromide] method, cytopathic effect reduction assay, and plaque reduction assay. The antiviral effect was further determined by flow cytometric analysis. The results showed that most of these extracts inhibited the propagation of herpes simplex virus types 1 and 2 (HSV-1 and HSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 28 publications
2
32
1
2
Order By: Relevance
“…Extracts from Lobophora variegate and Hydroclathrus clathra tus had higher activity than other algae extracts [71]. The extracts, inhibiting proliferation of HSV 1 and HSV 2 were characterized by a very low toxicity.…”
Section: Relationship Between the Structure Of Sulfated Polysaccharidmentioning
confidence: 85%
“…Extracts from Lobophora variegate and Hydroclathrus clathra tus had higher activity than other algae extracts [71]. The extracts, inhibiting proliferation of HSV 1 and HSV 2 were characterized by a very low toxicity.…”
Section: Relationship Between the Structure Of Sulfated Polysaccharidmentioning
confidence: 85%
“…There are more than 200 species of seaweeds in Hong Kong coastal water (Hodgkiss and Lee 1983) but there is limited research on their antiviral activity (Zhu et al 2003(Zhu et al , 2006. Our preliminary studies showed that some polysaccharide extracts from Hong Kong brown seaweeds possessed strong antiviral activity against herpes simplex viruses (Wang et al 2008). The polysaccharide fractions isolated from Hydroclathrus clathratus, a littoral alga of Hong Kong, showed the antiviral activities against HSV-2 (Wang et al 2007).…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, cell protection from the lethal effect of virus presence and propagation within the cellular compartment would ameliorate the disease impact and progression. Accordingly, the ability of any substance including medicinal extract to protect cell form the pathological effect of virus infection is desired and could be measured as a function of cell viability status following infection of the cells by virus inoculum (Wang et al, 2008). Thus, our evaluation for extract-induced protection from viral-induced cell cytopathic effects assay revealed that both AC and AF were capable of protecting viralinfected cells from the virus-induced cytopathy at EC 50 values of 4.63 and 51.76 µg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%